Tourism Object Development Strategy Sosopan Simpanglolo Hot Water (Sumatra Journal of Disaster, Geography and Geography Education, 2023)
This study aims to analyze the strategy for developing one of the tourist objects in Nagari Rabi Jonggor, Gunung Tuleh District, West Pasaman Regency. The Sosopan Simpanglolo Hot Springs is one of the health tourism destinations that is unique, different from other hot springs. This study shows that by using the quantitative SWOT analysis method which emphasizes the Internal Factor Analysis Summary (IFAS) matrix which includes strengths and weaknesses with a resulting score of 3.60. As for the External Factor Analysis Summary (EFAS), which includes opportunities and threats with a resulting score of 2.75. This shows that the Sosopan Simpanglolo Hot Springs has a sufficiently strong internal capacity to continue efforts to develop supporting infrastructure for tourism objects, by improving access to road facilities to tourist objects it will be able to increase internal resources which are its strengths. In its external capacity, Sosopan Simpanglolo Hot Springs can respond and take advantage of existing opportunities by encouraging the growth and development of the tourism industry and utilizing the natural potential of tourist attractions, to attract tourists to increase external resources which become opportunities by minimizing threats that exist at the location of tourist attractions. The results of this research study are expected to have implications for all parties to pay serious attention to the development of the Sosopan Simpanglolo Hot Springs tourist attraction.